Stakeholder workshop insights: Coffee value chain in Honduras - Colindres, Mirian (2023)
The initiative Rethinking Food Markets - CGIAR team organized a one-day stakeholders’ workshop for the WP1 global coffee value chain in Honduras. The workshop's main purpose was to bring together key stakeholders and potential partners to co-design innovations and interventions to implement the research study, to create a more equitable distribution of income and employment opportunities in growing food markets. During the workshop the participants had the chance to know about the results of the scoping study findings with stakeholders and validate these findings; they were also actively involved in the co-design of the set of innovations/interventions, as well as in the selection of the core innovations that could be improved and actively participate in the co-design of innovation/intervention packages; select and co-design core innovations for priority innovation areas to enhance impacts; and jointly identify potential activities for the years 2023-2024.